Effect of aspect ratio with roll moment derivative of a delta wing in supersonic flow - Crasta, Asha; Khan, Sher Afghan (IRA Publications, 2016)
In this paper attention is focussed on study of effect of Aspect ratio of the wing on roll moment derivatives at various angle of attack and Mach number for a Supersonic flow. It is been observed that there is a linear increment in rolling moment derivative with aspect ratio as well as with Angle of attack. The reason behind this being rolling moment derivative is a linear function of aspect ratio and angle of attack. The requirement for the validity of the present theory is the attachment of the shock at the leading edge of the wing. Whereas, in the case of detached shock wave, this theory is not valid.